2018
DOI: 10.1128/jcm.01691-17
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Validation of Three Molecular Devices for Simultaneous Detection and Identification of Influenza A and B and Respiratory Syncytial Viruses

Abstract: Rapid identification of respiratory pathogens, such as influenza virus A (FluA), influenza virus B (FluB), and respiratory syncytial virus (RSV), reduces unnecessary antimicrobial use and enhances infection control practice. We performed a comparative evaluation of three molecular methods: (i) the Aries Flu A/B & RSV, (ii) the Xpert Xpress Flu/RSV, and (iii) the Cobas Flu A/B & RSV assays. The clinical performances of the three methods were evaluated using 200 remnant nasopharyngeal swab (NPS) specimens agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…The ID NOW™ (previously Alere i) Influenza A & B assay (Abbott, San Diego, CA) was cleared by the US FDA for direct use on NP swabs as the first-ever Clinical Laboratory Improvement Amendments (CLIA)-waived nucleic acid-based test in January 2016 [64,65]. Similarly, the Xpert® Xpress Flu/RSV (Cepheid, Sunnyvale, CA) and cobas® Liat® Flu A/B & RSV (Roche Molecular Systems, Pleasanton, CA) assays are integrated nucleic acid extraction-independent devices that have recently received FDA clearance and CLIA-waiver for simultaneous detection and identification of FluA, FluB, and RSV in nasopharyngeal swabs [66]. The FilmArray® Respiratory EZ Panel (BioFire, Salt Lake City, UT) so far so far is the only CLIA-waived syndromic panel that covers a set of 14 respiratory viral and bacterial pathogens including classical coronavirus species [67].…”
Section: Future Directionmentioning
confidence: 99%
“…The ID NOW™ (previously Alere i) Influenza A & B assay (Abbott, San Diego, CA) was cleared by the US FDA for direct use on NP swabs as the first-ever Clinical Laboratory Improvement Amendments (CLIA)-waived nucleic acid-based test in January 2016 [64,65]. Similarly, the Xpert® Xpress Flu/RSV (Cepheid, Sunnyvale, CA) and cobas® Liat® Flu A/B & RSV (Roche Molecular Systems, Pleasanton, CA) assays are integrated nucleic acid extraction-independent devices that have recently received FDA clearance and CLIA-waiver for simultaneous detection and identification of FluA, FluB, and RSV in nasopharyngeal swabs [66]. The FilmArray® Respiratory EZ Panel (BioFire, Salt Lake City, UT) so far so far is the only CLIA-waived syndromic panel that covers a set of 14 respiratory viral and bacterial pathogens including classical coronavirus species [67].…”
Section: Future Directionmentioning
confidence: 99%
“…Newer, point-of-care test (POCT) polymerase chain reaction (PCR)-based commercial tests are now available. One such test is the cobas Liat influenza A/B and respiratory syncytial virus (RSV) assay (Roche, Basel, Switzerland) (Liat), an automated multiplex PCR system with time to result of 20 min [4]. Previous studies have found its performance to be excellent, with sensitivity/specificity in the region of 100%/97.1e100% for influenza A and 97.8%e100/99.5e99.7% for influenza B when fresh prospectively collected samples are tested [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…The Xpert Flu/RSV assay demonstrated high sensitivity and specificity compared with other molecular methods or traditional diagnosis tests (Chen et al, 2018;Cohen et al, 2018;Ling et al, 2018). Therefore, this assay has been approved for in vitro diagnosis of FluA, FluB and RSV infection in the USA and Europe, but not in China currently.…”
Section: Introductionmentioning
confidence: 99%